MeCP2 as a genome-wide modulator: the renewal of an old story - Della Ragione, Floriana; Filosa, Stefania; Scalabrì, Francesco; D'Esposito, Maurizio (Frontiers in Genetics, 2012)
Since the discovery of MECP2, its functions have attracted the interest of generations of molecular biologists. Its function as a transducer of DNA methylation, the major post-biosynthetic modification found throughout genomes, and its association with the neurodevelopmental disease Rett syndrome highlight its central role as a transcriptional regulator, and, at the same time, poses puzzling questions concerning its roles in physiology and pathology. The classical model of the MECP2 function predicts its role in gene specific repression through the binding of methylated DNA, via its interaction with the histone deacetylases and co-repressor complexes. This view has been questioned and, intriguingly, new roles for MECP2 as a splicing modulator and as a transcriptional activator have been proposed. Recent data have demonstrated that MECP2 is extremely abundant in the neurons, where it reaches the level of histone H1; it is widely distributed, tracking the methylated CpGs and regulates repetitive elements expression. The role of MECP2 in maintaining the global chromatin structure is further sustained by its involvement in other biologically relevant phenomena, such as the L1 repetitive sequences retrotransposition and the pericentromeric heterochromatin clustering during cellular differentiation. These new concepts renew the old view suggesting a role for DNA methylation in transcriptional noise reduction, pointing to a key role for MECP2 in the modulation of the genome architecture.